Pesquisa qualitativa em saúde mental: alguns apontamentos - Borges, Roselania Francisconi [UNESP]; Luzio, Cristina Amélia [UNESP] (My University, 2010)
This article proposes a reflection on the research´s process of mentalhealth highlighting the qualitative research as a fundamental resource for theproduction of knowledge about health / mental illness. From the theoreticalreference of historical and dialectical materialism it is supposed that the socialsciences´ object of study - the man as a historical being - is constantlychanging. Likewise it demands methodologies that can build analysis based inthe concrete reality of the subjects in their relations to produce life. From thisperspective, to reflect on mental illness and the ways of facing it can contributeto the formation of new concepts about care´s models nowadays: the asylummodel and the psychosocial.

Este artigo propõe uma reflexão sobre o processo de pesquisa em saúde mental destacando a pesquisa qualitativa como recurso fundamental para a produção de conhecimentos a respeito do processo saúde/doença mental. A partir do referencial teórico do materialismo histórico dialético parte-se da proposição de que o objeto de estudo das ciências sociais - o homem como ser histórico - está em constante transformação. Sendo assim, demanda metodologias que possam construir análises embasadas na realidade concreta dos sujeitos em suas relações para produzir a vida. Nesta perspectiva, refletir sobre o adoecimento psíquico e os modos de enfrentá-lo pode contribuir para a formação de novas concepções a respeito dos modelos de atenção atualmente vigentes: o modelo asilar e o psicossocial.
Qualitative research in mental health: some issues
Keywords: Qualitative research; Materialism historical dialectical method; Mental health; Psychosocial care; Pesquisa qualitativa; Saúde mental; Atenção psicossocial